MANAJEMEN MUTU KELAS DALAM MENINGKATKAN EFEKTIVITAS BELAJAR SISWA SEKOLAH DASAR - Nomi Gunawan; Susilawati; Dinny Mardiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze the implementation of class quality management in improving the effectiveness of student learning in elementary schools. The background of this study is the low effectiveness of learning caused by various factors, such as lack of student learning motivation, non-varied learning methods, less conducive learning environments, and limited classroom management by teachers. This study uses a qualitative approach with a case study method, which was carried out in two elementary schools, namely SDN Cijati and SDN Tanjungsari. Data collection was carried out using observation techniques, in-depth interviews, and documentation reviews. The results of the study indicate that well-planned and organized class quality management is able to create a more conducive learning environment, increase student involvement in the learning process, and encourage teachers to use more innovative learning methods and media. Supporting factors in the implementation of class quality management include support from the principal, regular teacher training, and parental involvement. Meanwhile, the challenges faced include limited facilities and infrastructure and the level of student heterogeneity. The conclusion of this study is that the implementation of systematic and sustainable class quality management contributes significantly to improving the effectiveness of student learning in elementary schools